Cultivation of Urochloa brizantha cv. Marandu in relation to the use of organic residues, biochars, and nitrogen fertilization - Alves, Marcelo Rodrigo; Souza, Janardelly Gomes de; Franco, Joice Moreira (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The objective of this study was to evaluate whether applications of organic residues and biochars, either individually or combined with nitrogen fertilization (NF), affect the development of Urochloa brizantha cv. Marandu. An experiment was set up in a completely randomized design (CRD), with a 7x4 factorial arrangement and 5 repetitions, consisting of: control soil (CS); soil + 300g of pure biosolids (PB); soil + 100g of pure sugarcane bagasse (PSB); soil + 150g of pure biosolids + 50g of pure sugarcane bagasse (PB+PSB); soil + 300g of biosolids biochar (BB); soil + 100g of sugarcane bagasse biochar (SBB); soil + 150g of biosolids biochar + 50g of sugarcane bagasse biochar (BB+SBB); and 4 levels of mineral nitrogen fertilization: 0; 12.5; 25; and 50 mg dm-3. Four harvests were conducted at 60, 88, 116, and 144 days after planting Urochloa brizantha cv. Marandu. Subsequently, the development of Marandu grass and the chemical attributes of the soil, after cultivation, were evaluated. Variance analysis (SISVAR software), mean comparison (Scott-Knott test p
Keywords: Biosolids